GAMBARAN MALOKLUSI DENGAN MENGGUNAKAN HMAR PADA PASIEN DI RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS SAM RATULANGI MANADO - Laguhi, Vigni Astria; Anindita, P. S.; Gunawan, Paulina N. (Universitas Sam Ratulangi, 2014)
Abstract: Malocclusions is a form of occlusions that deviates from the standard form which is accepted as a normal form and in Indonesia, the prevelence is still high enough. One of the ways to identify and assess the severity of malocclusions is using the Handicapping Malocclusion Assessment Record Index (HMAR). This study aims to describe the malocclusions patients of RSGM Unsrat using the HMAR index. This is a descriptive study conducted at the RSGM Unsrat Manado. Research subjects which totaled 34 patient study models. Malocclusions assessment obtained by examination of the study sample according to HMAR index include the tooth defect in one jaw, the second jaw teeth abnormalities relationship in a state of occlusions, and dentofasial defect. Result of research on the teeth in one jaw irregularities showed the highest percentage of tooth loss. Abnormal jaw relations in a state of second gear in the region of the anterior occlusion showed the highest percentage in the form of excessive biting distance and in the posterior region of highest form of canines more distally. Dentofacial abnormalities showed the highest percentage in the form of palatal bite. Research malocclusions severity based on HMAR index showed the highest percentage of severe malocclusions are in need of care.Keywords: Malocclusions, Handicapping Malocclusion Assessment Record Index Abstrak: Maloklusi adalah suatu bentuk oklusi yang menyimpang dari bentuk standar yang diterima sebagai bentuk normal dan di Indonesia prevalensinya masih cukup tinggi. Salah satu cara mengidentifikasi maloklusi dan menilai keparahan maloklusi tersebut menggunakan Indeks Handiccaping Assessment Record (HMAR). Penelitian ini bertujuan untuk mengetahui gambaran maloklusi pasien RSGM Unsrat menggunakan Indeks HMAR. Penelitian ini bersifat deskriptif dan dilakukan di RSGM Unsrat Manado. Subjek penelitian berjumlah 34 model studi pasien. Penilaian maloklusi diperoleh dengan pemeriksaan pada sampel penelitian berdasarkan indeks HMAR meliputi penyimpangan gigi dalam satu rahang, kelainan hubungan gigi kedua rahang dalam keadaan oklusi, dan kelainan dentofasial. Hasil penelitian pada penyimpangan gigi dalam satu rahang menunjukkan persentase tertinggi pada kehilangan gigi. Kelainan hubungan gigi kedua rahang dalam keadaan oklusi menunjukkan di regio anterior persentase tertinggi berupa jarak gigit berlebih dan diregio posterior tertinggi berupa gigi kaninus lebih ke distal. Kelainan dentofasial menunjukkan persentase tertinggi berupa palatal bite. Hasil penelitian tingkat keparahan maloklusi berdasarkan indeks HMAR menunjukkan persentase tertinggi pada maloklusi berat sangat memerlukan perawatan. Kata kunci: Maloklusi, Indeks Handicapping Malocclusion Assessment Record